Participación instituyente y política local mediante procesos y metodologías participativas : la construcción ciudadana del observatorio de la participación en Cuenca, Ecuador (2018)
ABSTRACT: This article retakes the relationship of the instituted participation and the instituting participation in a participatory process in the city of Cuenca-Ecuador province of Azuay, between the years 2017 and 2018. From an action research based on an exploratory case study, by using participatory and qualitative techniques were found as results that, (i) participatory methodologies enhance instituting participation, (ii) instituting participation promotes the adaptation and improvement of the systems of participation of local governments – an instituted participation, – and finally (iii), the participatory process generates proposals for direct, concrete and inclusive democratic practices.